KELAYAKAN USAHATANI JAGUNG HIBRIDA DI KABUPATEN MUNA PROVINSI SULAWESI TENGGARA - nFN Suharno; nFN Rusdin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
Feasibility Study of Hybrid Maize Farming in Muna District Southeast Sulawesi Province. Maize harvest area in 2015 in Muna District was 13,159 ha with the production by 32,007 tonnes and the productivity by 2.43 t/ha. This maize productivity is still considered low, due to the results of the study AIAT Southeast Sulawesi on 2014, wich able to obtain productivity by 5 tonnes of dry seed/ha. To increase the production of maize, advocacy anddissemination of technological innovations maize using hybrid varieties had been carried out. A research was applied to investigate the production of maize as well as the income of the farmers. Research was conducted using a structured interview with questionair to 30 maize hybrids farmers and 30 local maize farmers in the Wakobalu Agung Village,Kabangka Sub District, and Bente Village, Kabawo Sub District, Muna District in October to December 2015. The results showed that based on t test, the productivity of hybrid maize was significantly higher than the local variety, so the hybrid maize planting could increase of maize productivity. Hybrid farmers applied urea and NPK while the local maize growers did not use inorganic fertilizers. Organic fertilizer was applied both by hybrid maize and local maize group, yet dose of both groups respectively was varied. Hybrid maize farming with Bima 19 URI variety and local maize was feasible, each B/C 1.07 and 1.17. However the productivity and farmers’ income of the hybrid maize was higher than the local maize. The productivity of the hybrid maize by Bima 19 URI was 4,744 kg dry grain/ha and thefarmers’ income was IDR8,596,000. The productivity of the local maize was 1,404 kg dry grain/ha as well as farmers’ income was IRD4,666,000.Hybrid maize farming, productivity, farmers' incomeABSTRAKLuas panen jagung tahun 2015 di Kabupaten Muna yaitu 13.159 ha, dengan produksi 32.007 ton, produktivitas 2,43 t/ha. Produktivitas jagung yang dicapai selama ini dinilai masih rendah, mengingat hasil kajian BPTP Sulawesi Tenggara tahun 2014 sudah mampu diperoleh produktivitas 5 ton pipilan kering/ha. Untuk meningkatkan produksi jagung, maka telah dilakukan pendampingan dan penyebaran inovasi teknologi jagung menggunakan varietas hibrida. Berkenaan dengan hal tersebut maka dilakukan penelitian untuk mengetahui produksi dan pendapatan petani. Penelitian dilaksanakan dengan metoda wawancara terstruktur menggunakan kuesioner terhadap 30 petani jagung hibrida dan 30 petani jagung lokal di Desa Wakobalu Agung, Kecamatan Kabangka dan Desa Bente, Kecamatan Kabawo, Kabupaten Muna pada bulan Oktober – Desember 2015. Hasil penelitian menunjukkan bahwa berdasarkan uji t, diketahui bahwa produktivitas jagung hibrida yang ditanam petani berbeda nyata dengan produktivitas jagung lokal, sehingga penanaman jagung hibrida mampu mendorong peningkatan produktivitas jagung per hektar. Petani telah melakukan pemupukan urea dan NPK pada usahatani jagung hibridaBima 19 URI, hal ini tidak dilakukan oleh petani yang menanam jagung lokal. Namun demikian pupuk organik digunakan untuk usahatani jagung hibrida Bima 19 URI dan jagung lokal dengan dosis yang bervariasi. Usahatani jagung hibrida Bima 19 URI dan jagung lokal layak dan menguntungkan dengan masing nilai B/C 1,07 dan 1,17, 36 Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, Vol. 20, No.1, Maret 2017: 36-46 namun demikian produktivitas dan pendapatan usahatani jagung hibrida lebih tinggi daripada usahatani jagung lokal. Produktivitas jagung hibrida Bima 19 URI sebesar 4.744 kg pipilan kering/ha dengan nilai pendapatan Rp8.596.000, sedangkan produktivitas jagung lokal sebesar 1.404 kg pipilan kering/ha dengan nilai pendapatan Rp4.666.000.Usahatani jagung hibrida, produktivitas, pendapatan petani